The Wright brothers - Rich, Richard; Nissen, Brian, 1939-; Nest Entertainment, Inc.; Rich Animation Studios (Coppell, TX : NEST Family Entertainment, 2005)
Animated biography of the Wright brothers, two men who ignored all those who said it couldn't be done and became the first to manage powered flight.
Title from container.
"NEST complete learning system"--Container.
Includes Resource & Activity Book.
"Interactive DVD packed with bous features"--Container.
Website access feature requires a computer with DVD drive and Internet access. Computer is not required for other DVD-video bonus features"--Container.
Music, Lex De Azevedo.
Keywords: Wright, Orville, -- 1871-1948 -- Juvenile films; Wright, Wilbur, -- 1867-1912 -- Juvenile films; Wright, Orville, -- 1871-1948.; Wright, Wilbur, -- 1867-1912.; Inventors -- United States -- Biography -- Juvenile films; Aeronautics -- United States -- Biography -- Juvenile films; Inventors -- United States -- Biography; Aeronautics -- United States -- History; Children's films; Animated films; Video recordings for the hearing impaired